Radon Transformation Applied to the Segmentation of Grayscale Digital Images (2018)
In this scientific research article, the community interested in digital image processing is introduced to the new application of Radon’s transformation to segment images in grayscale, which allows the identification and classification of regions or objects, which can be extended to color images. Results obtained were compared with the results of two classic segmentation algorithms: the optimized Otsu thresholding algorithm, and the Seeded Region Growing growth algorithm.